Positive harmonisation of national criminal law: Necessary or essential for mutual recognition? - Rus, Andrei Claudiu (European journal of probation, 2024)
Positive harmonisation of criminal law should only be a subsidiary means of implementing the principle of mutual recognition. Regarding criminal procedural law, this is laid down in Art. 67 TFEU (‘if necessary’) and in Art. 82(2) TFEU (‘to the extent necessary’). However, the effectiveness of the principle of mutual trust depends on the harmonisation of the national laws of the Member States, especially in cases when the national law of the executing State does not regulate at all aspects that may affect the nature or aggravate the sentence which is to be recognised. In this context, we will try to show that, if the alternative execution modality of a custodial sentence is not at all regulated in the national law of the executing State, its recognition and enforcement, with the consequent continuous deprivation of liberty of the sentenced person, could be considered an aggravation of the sentence and thus a violation of Article 8(4) of FD 2008/909. The paper thus highlights not only the differences between the legal frameworks of some Member States, but also how the lack of regulation on alternative execution modalities to custodial sentences or probation measures and alternative sanctions could stand in the way of reaching the purposes of Framework Decisions 2008/909 and 2008/947. On the other hand, we will show that although the framework decisions cannot have a direct effect, when applying national law, the national authorities are therefore required to interpret it, to the greatest extent possible, in light of the text and the purpose of the framework decision in order to achieve the result sought by that decision.